The Effect of Professional Skepticism, Independence and Auditor Ethics on Fraud Prevention by Moderating Audit Quality (Study at Public Accountant Firm Jojo Sunarjo and Partners) - Aprianto, Hary; Nur, Basyiruddin; Karsam, Karsam (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The purpose of this research is to determine the influence of Professional Skepticism, Independence, and Auditor Ethics on Fraud Prevention moderated by Audit Quality. The research method used is a quantitative research approach. The data for this research was obtained from the distribution of questionnaires to all JS & R Public Accountant Offices, totaling 100 Auditor respondents. The analysis technique used was PLS SEM version 4. Based on the research results, it is stated that Professional Skepticism has a positive and significant effect on Fraud Prevention with a path coefficient value of 0.307 and a p-value of 0.018. Independence has a positive and significant effect on Fraud Prevention with a path coefficient value of 0.238 and a p-value of 0.013. Auditor Ethics has a significant positive effect on Fraud Prevention with a path coefficient value of 0.256 and a p-value of 0.002. Audit Quality moderates the effect of Professional Skepticism on Fraud Prevention with a path coefficient value of 0.286 and a p-value of 0.004. Audit Quality moderates the effect of Independence on Fraud Prevention with a path coefficient value of -0.304 and a p-value of 0.025. Audit Quality does not moderate the effect of Auditor Ethics on Fraud Prevention with a path coefficient value of 0.028 and a p-value of 0.374.